(untitled) (Research Announcements "Heritage BG", 2025)
This article applies an inductive method to the phenomenon of Bulgarian literary modernism; this method aims not to check the validity of already-existing models, but to create a new theory of its own. The path it follows is from the bottom up, from the text to the generalization, from the margins to the center. A diachronic and synchronic cross section of Bulgarian literary modernism has been made, while many of the questions the article discusses have been raised for the first time and are examined in a new light. References: Antov, Plamen. (2018). Obratnata poetika na 80-te: Nadolu, navatre, nazad. In: „Vladetelyat na chudoto. Sbornik v chest na 50-godishninata na Georgi Rupchev. Sofia. 161–169. Eliade, M. (1994). Mitat za vechnoto zavrashtane. Sofia. Hadzhikosev, S. (1979). Balgarskiyat simvolizam. Sofia. Krastev, K. (1927). Dzhaz-banda. In: v-k „Iztok“, 57, 19.02.1927, 2. Markham, R. (1931). Meet Bulgaria. Sofia. Mineva (Petkanova), M. (1927). Makedonski pesni. Sofia. Nitsolov, L., & Georgiev, L. (1980). Rechnik na literaturnite termini. Sofia. Vezenkov, E. (1938). Radiopublika. In: sp. „Zlatorog“, ХХ, 6.